Humanity concept in social sciences - Barbosa de Magalhães, Valéria (Sociedad y Economía, 2010)
This article intends to analyze the fragility of the concept of humanity in social sciences, especially for the classical opposition between nature and culture. For instance, the human efforts to be distinguished from animals seem to be based on our deepest intention to dominate nature.